MINIMIZING DEFAULT THROUGH SYARIAH FINTECH IN ORDER TO PROVIDE ACCESS TO FUNDING FOR BUSINESS ACTORS - Nurhilmiyah, Nurhilmiyah; Purba, Hasim; Sitompul, Zulkarnain; Azwar, Tengku Keizerina Devi (Proceeding International Seminar of Islamic Studies, 2024)
One of the main problems experienced by information technology-based co-funding services is the high amount of loan interest from the organizer. This resulted in a pile of interest that never finished and eventually became a default and was determined to be in default. The beneficiary fails to pay the funds along with interest. This is considered burdensome and it is necessary to find alternative funding services that do not charge high interest to users. This article aims to solve the problem of minimizing default through Islamic financial technology to provide access for business actors. The concept of financing through syariah fintech companies is a solution and answer for business actors, especially MSMEs, regarding the complexity of capital and without determining interest from the lender. All will be determined through an agreement that has been agreed between the funder and the recipient of funds. The agreed agreement is also not the same from one another, which is based on the allocation of funds from the loan applicant. The difference between Islamic and conventional fintech in reducing risk can be clearly seen. That is, if in conventional fintech is to raise interest as a form of prudence. So that the absence of interest will be the main attraction for syariah fintech. The method used in this paper is literature research. The result is the minimization of defaults by fund recipients through Islamic financial technology to provide financial access for business actors.